The Inhibitor of wax 1 locus (Iw1) prevents formation of β‐ and OH‐β‐diketones in wheat cuticular waxes and maps to a sub‐cM interval on chromosome arm 2BS. (25th April 2013) - Adamski, Nikolai M.; Bush, Maxwell S.; Simmonds, James; Turner, Adrian S.; Mugford, Sarah G.; Jones, Alan; Findlay, Kim; Pedentchouk, Nikolai; von, Penny; Uauy, Cristobal
Summary Glaucousness is described as the scattering effect of visible light from wax deposited on the cuticle of plant aerial organs. In wheat, two dominant genes lead to non‐glaucous phenotypes: Inhibitor of wax 1 (Iw1) and Iw2. The molecular mechanisms and the exact extent (beyond visual assessment) by which these genes affect the composition and quantity of cuticular wax is unclear. To describe the Iw1 locus we used a genetic approach with detailed biochemical characterization of wax compounds. Using synteny and a large number of F2 gametes, Iw1 was fine‐mapped to a sub‐cM genetic interval on wheat chromosome arm 2BS, which includes a single collinear gene from the corresponding Brachypodium and rice physical maps. The major components of flag leaf and peduncle cuticular waxes included primary alcohols, β‐diketones and n‐alkanes. Small amounts of C19–C27 alkyl and methylalkylresorcinols that have not previously been described in wheat waxes were identified. Using six pairs of BC2F3 near‐isogenic lines, we show that Iw1 inhibits the formation of β‐ and hydroxy‐β‐diketones in the peduncle and flag leaf blade cuticles. This inhibitory effect is independent of genetic background or tissue, and is accompanied by minor but consistent increases in n‐alkanes and C24 primary alcohols. No differences were found in cuticle thickness and carbon isotope discrimination in near‐isogenic lines differing at Iw1.